N-methyl-D-aspartate receptor antagonists disrupt the formation of a mammalian neural map. - Simon, D K (1992)
The topographic ordering of retinal connections in the rat superior colliculus emerges during early postnatal life from an initially diffuse projection. Disruption of N-methyl-D-aspartate (NMDA) receptor activity in the superior colliculus during this period interferes with map remodeling. In rats chronically treated with NMDA receptor antagonists during the first two postnatal weeks, aberrant axons remain and arborize at topographically incorrect sites. These results indicate that, at a stage preceding visually evoked activity, normal NMDA receptor function is important for the development of an ordered neural map in the mammalian brain.